Carbon-coated nanotube lithium titanate / carbon composite negative electrode material, preparation method and lithium ion battery
By introducing carbon-coated nanotube-like structures on lithium titanate, the problems of slow diffusion and poor conductivity of LTO lithium ions are solved, and its high rate performance and conductivity are significantly improved.
Patent Information
- Application Number
- CN202411519365.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-11
AI Technical Summary
The slow diffusion and poor conductivity of lithium titanate (LTO) limit its high rate performance.
The preparation method of carbon-coated nanotube lithium titanate/carbon composite anode material is adopted. By introducing a nanotube structure on lithium titanate and carbon coating, its conductivity and lithium ion diffusion ability are improved.
The conductivity and lithium ion diffusion speed of LTO are significantly improved, its high-rate performance is enhanced, and by inhibiting particle growth, the smaller particle size is maintained and the lithium diffusion pathway is reduced.
Smart Images

Figure CN119419237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material, a preparation method and a lithium ion battery. Background Art
[0002] As the concept of low-carbon living becomes popular, electric vehicles, such as plug-in hybrid electric vehicles (PHEV), hybrid electric vehicles (HEV), and pure electric vehicles (EV), are becoming more and more popular. These electric vehicles rely on high-performance and high-safety energy storage devices (ESD), and therefore place higher demands on power batteries, which are the core components of electric vehicles. Lithium-ion batteries (LIBs) are rechargeable power sources whose electrochemical properties, especially safety and cycle life, are highly dependent on the performance of negative electrode materials. In order to improve the power density, cycle life, and safety of lithium-ion batteries, researchers continue to develop and innovate negative electrode materials.
[0003] Lithium titanate (Li4Ti5O 12 , LTO for short) is a negative electrode material with excellent performance. Its discharge platform is higher than 1.55V, which can avoid lithium dendrite deposition and electrolyte reduction, thereby extending the cycle life and improving safety. In addition, LTO also has the characteristic of "zero strain", that is, the volume change is extremely small during the lithium insertion and deinsertion process, ensuring good structural stability and reversibility. However, LTO also has some defects, such as slow lithium ion diffusion and poor electrical conductivity, which limit its high-rate performance. To solve this problem, researchers have used methods such as nanodesign and surface coating to improve the performance of LTO. Nanodesign can reduce the migration distance of electrons and ions in LTO and accelerate the reaction kinetics. Surface coating (especially composite design with carbon materials such as amorphous carbon, carbon nanotubes and graphene) can significantly improve the conductivity of LTO and prevent its agglomeration.
[0004] Therefore, it is of great significance to study carbon-coated nanostructured lithium titanate composite negative electrode materials with low production cost and green and pollution-free. This material is not only expected to overcome the inherent defects of LTO, but also to further improve the overall performance of lithium-ion batteries, providing strong support for the development of green transportation modes such as electric vehicles. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a method for preparing a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material to improve the problems of slow lithium ion diffusion and poor electrical conductivity of lithium titanate.
[0006] The present invention solves another technical problem and provides a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material and a lithium-ion battery prepared using the carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material.
[0007] The technical solution of the present invention is:
[0008] A method for preparing a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material, wherein the specific operation of the method is as follows:
[0009] (1) Disperse an organic carbon source, hexadecyltrimethylammonium bromide (CTAB), butyl titanate and a lithium source in 25 ml of an organic solvent and stir thoroughly;
[0010] (2) Add 5 ml of water to the solution in step (1), stir rapidly, and then transfer to a reactor for solvothermal reaction to obtain lithium titanate / carbon Li4Ti5O 12 / C precursor;.
[0011] (3) washing, drying and then grinding the product in step (2) to obtain a gray powder;
[0012] (4) The lithium titanate / carbon Li4Ti5O obtained in step (3) 12 The / C precursor is calcined in an argon atmosphere to obtain a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material.
[0013] As a preference, the method comprises the following steps:
[0014] (1) 1-3 mmol of an organic carbon source and 2 mmol of hexadecyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of an organic solvent solution, subjected to ultrasonication for 30 min, and vigorously stirred for 10 min to obtain a solution A; butyl titanate and a lithium source were added to the solution A, respectively, and stirred at room temperature for 12-18 h to obtain a solution B;
[0015] (2) Add 5 ml of water to solution B and stir rapidly to obtain solution C;
[0016] (3) Transfer solution C to a 50 ml reactor and heat at 180-240° C. for 24-48 h to obtain precipitate D;
[0017] (4) After the reaction is completed, the mixture is cooled to room temperature, washed with water and ethanol for several times, and calcined at 600-800° C. for 6-12 h in an argon atmosphere.
[0018] Preferably, the present invention uses cheap and readily available organic carbon as a carbon source and introduces carbon by an in-situ carbon coating method. The carbon source, carbon content and thickness will affect the performance of the spinel structure lithium titanate electrode.
[0019] Preferably, the organic carbon source used in step (1) is glucose and citric acid.
[0020] Preferably, the organic solvent used in step (1) is anhydrous ethanol, a mixture of anhydrous ethanol and ethylene glycol (volume ratio 1:1 or 3:1), or ethylene glycol.
[0021] Preferably, the lithium source used in step (1) is one of lithium hydroxide monohydrate, lithium nitrate and lithium carbonate.
[0022] Preferably, the lithium source and butyl titanate used in step (1) are mixed in a ratio of n(Li / Ti)=0.8-1.2.
[0023] The carbon-coated nanotube lithium titanate / carbon composite negative electrode material prepared by the above method exhibits a unique nanotube structure, which is composed of nanoparticles connected to each other and covered with a carbon layer on the surface, with gaps between the nanoparticles;
[0024] Preferably, the carbon-coated nanotubular lithium titanate / carbon composite negative electrode material is a composite material formed by nanotubular lithium carbonate and amorphous carbon; the nanotubular lithium carbonate has a length of 2 μm and a diameter of 150-300 nm; each nanotube is composed of nanoparticles that are interconnected and covered with a carbon layer on the surface, and there are gaps between the nanoparticles; the nanotubular lithium carbonate / carbon composite is distributed in an orderly manner.
[0025] The lithium-ion battery prepared using the above-mentioned carbon-coated nanotubular lithium titanate / carbon composite negative electrode material is characterized in that the carbon-coated nanotubular lithium titanate / carbon composite negative electrode material, acetylene black and PVDF are mixed in N-methylpyrrolidone at a mass ratio of 8:1:1, and coated on copper foil to make a 14mm circular pole piece, and assembled to obtain a lithium-ion battery.
[0026] Advantages of the present invention:
[0027] (1) Nanotubular lithium carbonate is beneficial for shortening Li + The distance an ion travels in a crystal.
[0028] (2) The coating not only enhances the electronic conductivity of LTO, but also inhibits the growth of LTO particles during annealing, making their size relatively small, thereby reducing the lithium diffusion pathway.
[0029] (3) The synergistic effect of carbon and lithium titanate can further improve the electron / ion transport kinetics during the charge and discharge process.
[0030] (4) The method of the present invention is simple to operate, environmentally friendly and highly feasible.
[0031] (5) The carbon-coated nanotube lithium titanate / carbon (LTO / C) composite negative electrode material prepared by the present invention has excellent electrochemical performance. Figure 3The discharge capacities of the materials prepared by the method as shown in a) at 1C, 2C, 5C, 10C, 15C, and 20C are 181.5, 178.6, 173.7, 167.6, 160.7, and 154.7 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the present disclosure, the following briefly introduces the drawings required to be used in some embodiments of the present disclosure. Obviously, the drawings described below are only drawings of some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can also be obtained based on these drawings. In addition, the drawings described below can be regarded as schematic diagrams, and are not limitations on the actual size of the product involved in the embodiments of the present disclosure, the actual process of the method, the actual timing of the signal, etc.
[0033] Figure 1 XRD patterns of the LTO / C composites obtained in Examples 1-4 (b, c, a, d);
[0034] Figure 2 is a SEM image of the LTO / C composite obtained in Example 3;
[0035] Figure 3 The rate performance diagram of the LTO / C composite obtained in Example 1-4 (b, c, a, d);
[0036] Figure 4 is a cycle curve diagram of the LTO / C composite obtained in Example 3 at 20°C; DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solutions in this application, the following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0038] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0039] The present invention will be further described below with reference to specific examples.
[0040] Example 1
[0041] (1) 1 mmol of glucose and 2 mmol of cetyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of anhydrous ethanol solution, ultrasonicated for 30 min, and vigorously stirred for 10 min to obtain solution A.
[0042] (2) To the solution (1) were added lithium hydroxide monohydrate and butyl titanate (1.7 ml) in a molar ratio of 1:1, and the mixture was stirred at room temperature for 15 h.
[0043] (3) Add 5 ml of water to the homogeneous solution (2) and stir rapidly for 2 min. Then transfer the solution to a 50 ml reactor and heat at 180 °C for 24 h.
[0044] (4) The precipitate obtained in (3) was washed three times with water and ethanol respectively, dried in an oven at 60°C to obtain a dry solid, and the solid was ground into powder in a mortar.
[0045] (5) The powder obtained in (4) was calcined at 600° C. for 8 h under Ar atmosphere protection to obtain a LTO / C composite.
[0046] The XRD pattern of the obtained product is shown in Figure 1 As shown in b, the obtained diffraction peaks are consistent with the standard peaks of spinel lithium titanate (JCPDS NO.49-0207) and there are no impurity peaks. Figure 3 Figure b is the rate performance diagram of the LTO / C composite.
[0047] Preparation of negative electrode sheet for lithium-ion battery:
[0048] The prepared LTO / C composite, PVDF and acetylene black were mixed in a mass ratio of 8:1:1 and ground evenly in a mortar, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added and continued to grind until it was bright and uniform.
[0049] After mixing evenly, apply it evenly on a clean and dry copper foil with a film applicator, and then dry it in a vacuum oven at 90°C for 12 hours.
[0050] After drying, the copper foil was made into a 14 mm circular electrode using a punching machine and then placed in a vacuum oven at 120°C for 12 h.
[0051] Preparation of lithium-ion batteries:
[0052] The entire process of lithium-ion battery assembly is completed in a glove box filled with argon. The battery consists of four parts: lithium sheet as the negative electrode of the battery, the prepared material as the positive electrode, the 2300 diaphragm of Celgard Company of the United States as the diaphragm, and 1.0M EC-DMC (volume ratio of 1:1) as the electrolyte. The assembly order of CR2032 model battery is from bottom to top. First, place the negative electrode (lithium sheet) in the center of the negative electrode shell, drop two drops of electrolyte, then put a layer of diaphragm, then drop two drops of electrolyte on the diaphragm, and then place the negative electrode sheet on the diaphragm (the side coated with the negative electrode material is placed facing the diaphragm), then place the gasket, shrapnel, and positive electrode shell in turn, press the package with insulating tweezers, and then seal it with appropriate pressure with a sealing machine, and let it stand for 24 hours for electrochemical performance testing.
[0053] Example 2
[0054] (1) 3 mmol of citric acid and 2 mmol of cetyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of ethylene glycol solution, ultrasonicated for 30 min, and vigorously stirred for 10 min to obtain solution A.
[0055] (2) Lithium carbonate and butyl titanate (1.7 ml) in a molar ratio of 0.8:1 were added to the solution (1), and the mixture was stirred at room temperature for 15 h.
[0056] (3) Add 5 ml of water to the homogeneous solution (2) and stir rapidly for 2 min. Then transfer the solution to a 50 ml reactor and heat at 200 °C for 36 h.
[0057] (4) The precipitate obtained in (3) was washed three times with water and ethanol respectively, dried in an oven at 60°C to obtain a dry solid, and the solid was ground into powder in a mortar.
[0058] (5) The powder obtained in (4) was calcined at 800°C for 10 h under Ar atmosphere to obtain a LTO / C composite. The XRD pattern of the obtained product is shown in Figure 1 As shown in c. Figure 3 Figure c is the rate performance diagram of the LTO / C composite.
[0059] Example 3
[0060] (1) 2 mmol of glucose and 2 mmol of cetyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of anhydrous ethanol and ethylene glycol (volume ratio 3:1), ultrasonicated for 30 min, and vigorously stirred for 10 min to obtain solution A.
[0061] (2) To the solution (1) were added lithium hydroxide monohydrate and butyl titanate (1.7 ml) at a molar ratio of 1.2:1, and the mixture was stirred at room temperature for 15 h.
[0062] (3) Add 5 ml of water to the homogeneous solution (2) and stir rapidly for 2 min. Then transfer the solution to a 50 ml reactor and heat at 180 °C for 36 h.
[0063] (4) The precipitate obtained in (3) was washed three times with water and ethanol respectively, dried in an oven at 60°C to obtain a dry solid, and the solid was ground into powder in a mortar.
[0064] (5) The powder obtained in (4) was calcined at 600°C for 6 h under Ar atmosphere to obtain LTO / C composite. The XRD pattern of the obtained product is shown in Figure 1 As shown in a in . Figure 3 a in FIG. is the rate performance diagram of the LTO / C composite.
[0065] like Figure 4 As shown in Figure 2, the composite catalyst synthesized in Example 3 was applied to a lithium-ion battery and a cycle performance test was performed at a current density of 20C. After 800 cycles of charge and discharge, the discharge specific capacity of the composite material remained at 145.4 mAh g -1 , compared with the capacity before cycling (151.1 mAh g -1 ) retention rate is 96.5%. Coulomb efficiency is basically maintained at 100%.
[0066] Example 4
[0067] (1) 2 mmol of citric acid and 2 mmol of cetyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of anhydrous ethanol and ethylene glycol (volume ratio 1:1), ultrasonicated for 30 min, and vigorously stirred for 10 min to obtain solution A.
[0068] (2) Lithium nitrate and butyl titanate (1.7 ml) in a molar ratio of 1:1 were added to the solution (1), and the mixture was stirred at room temperature for 15 h.
[0069] (3) Add 5 ml of water to the homogeneous solution (2) and stir rapidly for 2 min. Then transfer the solution to a 50 ml reactor and heat at 240 °C for 48 h.
[0070] (4) The precipitate obtained in (3) was washed three times with water and ethanol respectively, dried in an oven at 60°C to obtain a dry solid, and the solid was ground into powder in a mortar.
[0071] (5) The powder obtained in (4) was calcined at 800°C for 12 h under Ar atmosphere to obtain a LTO / C composite. The XRD pattern of the obtained product is shown in Figure 1 As shown in d. Figure 3 Figure d in the figure is the rate performance diagram of the LTO / C composite.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0073] The above describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claim involved.
[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material, characterized in that: The specific operation of the method is: (1) Disperse an organic carbon source, hexadecyltrimethylammonium bromide (CTAB), a lithium source and butyl titanate in 25 ml of an organic solvent and stir thoroughly; (2) Add 5 ml of water to the solution in step (1), stir rapidly, and then transfer to a reactor for solvothermal reaction to obtain lithium titanate / carbon Li4Ti5O 12 / C precursor; (3) washing, drying and then grinding the product in step (2) to obtain a gray powder; (4) The lithium titanate / carbon Li4Ti5O obtained in step (3) 12 The / C precursor is calcined in an argon atmosphere to obtain a carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: (1) 1-3 mmol of an organic carbon source and 2 mmol of hexadecyltrimethylammonium bromide (CTAB) were dissolved in 25 ml of an organic solvent solution, subjected to ultrasonication for 30 min, and vigorously stirred for 10 min to obtain a solution A; butyl titanate and a lithium source were added to the solution A, respectively, and stirred at room temperature for 12-18 h to obtain a solution B; (2) Add 5 ml of water to solution B and stir rapidly to obtain solution C; (3) Transfer solution C to a 50 ml reactor and heat at 180-240° C. for 24-48 h to obtain precipitate D; (4) After the reaction is completed, the mixture is cooled to room temperature, washed with water and ethanol for several times, and calcined at 600-800° C. for 6-12 h in an argon atmosphere.
3. The preparation method according to any one of claims 1-2, characterized in that: The organic carbon sources used in step (1) are glucose and citric acid.
4. The preparation method according to any one of claims 1 to 2, characterized in that: The organic solvent used in step (1) is anhydrous ethanol, a mixture of anhydrous ethanol and ethylene glycol (volume ratio 1:1 or 3:1), and ethylene glycol.
5. The preparation method according to any one of claims 1 to 2, characterized in that: The lithium source used in step (1) is one of lithium hydroxide monohydrate, lithium nitrate and lithium carbonate.
6. The preparation method according to any one of claims 1-2, characterized in that: The lithium source and butyl titanate used in step (1) are mixed in a ratio of n(Li / Ti)=0.8-1.
2.
7. A carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material prepared by the method according to any one of claims 1 to 2, characterized in that: It presents a unique nanotube structure, which is composed of nanoparticles that are interconnected and covered with a carbon layer on the surface, with gaps between the nanoparticles.
8. A lithium-ion battery prepared using the carbon-coated nano-tubular lithium titanate / carbon composite negative electrode material according to claim 7, characterized in that: The carbon-coated nanotubular lithium titanate / carbon composite negative electrode material, acetylene black and PVDF were mixed in N-methylpyrrolidone at a mass ratio of 8:1:1, coated on copper foil and made into a 14 mm circular electrode piece, and assembled into a lithium-ion battery.
Citation Information
Cited By
Preparation method of lithium ion battery cathode material copper-based lithium titanate with high rate capability
CN120319793A
Nitrogen-doped carbon-coated titanium niobate negative electrode material as well as preparation method and application thereof
CN121011645A
Multistage nanostructure and double-phase boundary Co-Li4Ti5O12 / TiO2 / C composite material as well as preparation method and application thereof
CN121225647A